2016
DOI: 10.1186/s12864-016-2708-0
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial transmission of Clostridium difficile ribotype 027 in a Chinese hospital, 2012–2014, traced by whole genome sequencing

Abstract: BackgroundThe rapid spread of Clostridium difficile NAP1/BI/027 (C. difficile 027) has become one of the leading threats of healthcare-associated infections worldwide. However, C. difficile 027 infections have been rarely reported in Asia, particularly in China.ResultsIn this study, we identified a rare C. difficile bloodstream infection (BSI) from three isolates of a patient during repeated hospital admission. This finding triggered a retrospective epidemiological study to scan all cases and strains emerged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
3
30
0
1
Order By: Relevance
“…A convenient alternative to SNP-based genotyping is offered by the commercial software SeqSphere, which implements a 85 core genome multilocus sequence typing scheme (cgMLST) for the analysis of genomic diversity in C. difficile 18 and other organisms. Indeed, cgMLST 18 confirmed the prior conclusion from genomic SNP analyses 19 that a common clone of C. difficile had been isolated over two successive years at a hospital in China. However, we are not aware of a quantitative comparison of the sensitivity of both methods.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…A convenient alternative to SNP-based genotyping is offered by the commercial software SeqSphere, which implements a 85 core genome multilocus sequence typing scheme (cgMLST) for the analysis of genomic diversity in C. difficile 18 and other organisms. Indeed, cgMLST 18 confirmed the prior conclusion from genomic SNP analyses 19 that a common clone of C. difficile had been isolated over two successive years at a hospital in China. However, we are not aware of a quantitative comparison of the sensitivity of both methods.…”
Section: Introductionsupporting
confidence: 75%
“…Multiple bacterial strains from local outbreaks of C. difficile disease in hospitals in Oxfordshire and China differ by very few SNPs 13,15,19 . The published data indicates a 95% probability that the genomes of pairs of strains from a transmission chain differ by two non-recombinant SNPs, or less 13 .…”
Section: Suitability Of Cgmlst For Epidemiological Analyses Of Transmmentioning
confidence: 99%
See 1 more Smart Citation
“…For C. difficile, initial studies also confirmed the general applicability of WGS-based typing (9,15,16). Nevertheless, the broad use of WGS-based typing of C. difficile is still hampered by the lack of standardized nomenclature (17); this has already been established for other pathogens (18)(19)(20)(21) and would facilitate interlaboratory exchange of data.…”
mentioning
confidence: 85%
“…Moreover, in consideration of the complex personnel mobility in medical institutions, the majority of CDI is hospital-acquired, and nosocomial transmission of C. difficile contributes greatly to the spread of different genotypes. Recently, whole genome sequencing (WGS) identified the dissemination and spread of C. difficile ribotype 027 (RT027) and sequence type 081 (ST081) in two Chinese hospitals [8,9]. Therefore, a better understanding of regional epidemiology is helpful to guide priorities for the management of hospital-acquired Clostridium difficile infection (HA-CDI).…”
Section: Introductionmentioning
confidence: 99%